2010
DOI: 10.1021/ac101006h
|View full text |Cite
|
Sign up to set email alerts
|

Speciation of Individual Mineral Particles of Micrometer Size by the Combined Use of Attenuated Total Reflectance-Fourier Transform-Infrared Imaging and Quantitative Energy-Dispersive Electron Probe X-ray Microanalysis Techniques

Abstract: Our previous work demonstrated for the first time the potential of the combined use of two techniques, attenuated total reflectance FT-IR (ATR-FT-IR) imaging and a quantitative energy-dispersive electron probe X-ray microanalysis, low-Z particle EPMA, for the characterization of individual aerosol particles. In this work, the speciation of mineral particles was performed on a single particle level for 24 mineral samples, including kaolinite, montmorillonite, vermiculite, talc, quartz, feldspar, calcite, gypsum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 34 publications
1
38
0
Order By: Relevance
“…They exist in many different forms, including Na-feldspar, Kfeldspar, muscovite, montmorillonite, illite, Mg-vermiculite, kaolinite, talc, pyrophyllite, etc. (Jung et al, 2010;Malek et al, 2011). Most of them belong to clay mineral.…”
Section: Mineral Dust Particlesmentioning
confidence: 99%
“…They exist in many different forms, including Na-feldspar, Kfeldspar, muscovite, montmorillonite, illite, Mg-vermiculite, kaolinite, talc, pyrophyllite, etc. (Jung et al, 2010;Malek et al, 2011). Most of them belong to clay mineral.…”
Section: Mineral Dust Particlesmentioning
confidence: 99%
“…In many cases, airborne particles are internal mixtures of two or more chemical species, for which X-ray analysis is even more difficult. Recently, our group reported that various types of individual airborne particles could be identified clearly by the combined use of low-Z particle EPMA and attenuated total reflectance Fourier transform infrared spectroscopy (ATR-FTIR) imaging, where both the elemental chemical composition and molecular species of the same individual particles can be obtained from their X-ray and ATR-FTIR spectral data (Jung et al, 2010;Malek et al, 2011). Low-Z particle EPMA and ATR-FTIR imaging can provide complementary information on their morphology and elemental concentrations, as well as their molecular species, functional groups, crystal structure, and physical phase of the same individual particles, respectively.…”
Section: Y-c Song Et Al: Investigation Of Aged Asian Dust Particlesmentioning
confidence: 99%
“…Low-Z particle EPMA and ATR-FTIR imaging can provide complementary information on their morphology and elemental concentrations, as well as their molecular species, functional groups, crystal structure, and physical phase of the same individual particles, respectively. The combined use of these two techniques resulted in a better understanding of the physicochemical characteristics of individual mineral, aged sea salt, and secondary aerosol particles than when the techniques were used alone (Jung et al, 2010;. In this study, an Asian dust sample collected on 11 November 2002 was examined again to obtain detailed physicochemical characteristics of the aged Asian dust particles, which experienced extensive chemical modification during long-range transport, by the combined application of low-Z particle EPMA and ATR-FTIR imaging.…”
Section: Y-c Song Et Al: Investigation Of Aged Asian Dust Particlesmentioning
confidence: 99%
See 1 more Smart Citation
“…Note, however, that band positions could be slightly or considerably shifted from reported band wave numbers obtained by both TIR and ATR techniques (Wada, 1967;Farmer, 1974;Van der Marel and Beutelspacher, 1976;Hlavay et al, 1978;Madejová and Komadel, 2001;Schroeder, 2002;Vaculícová and Plevová, 2005;Jung et al, 2010) due to the different infrared methods (i.e., TIR, DRIFT, ATR FTIR), sample preparation (pressed pellet or powder sample), changing chemistry of minerals (i.e., Mg incorporation in calcite; different cation occupancy in layers and interlayers of smectite etc.) and anisotropy of infrared absorption (in which certain indicatrix section(s) may become dominant during analysis).…”
Section: Atr Ftirmentioning
confidence: 87%